Efek Bahan Ajar IPA Terpadu Sistem Pernapasan dan Ekskresi Terintegrasi Strategi CTL pada Kinerja Akademik Siswa SMP - Wiwit Mila Sari; Asrizal Asrizal*; Renol Afrizon (Universitas Syiah Kuala, 2022)
The 21st century demands quality human resources and they have good performance. The goal of the 21st century is to produce people who have the ability to think critically, have strong character, and use information and communication technology. This ability can be developed in the integrated science learning process. However, the implementation of integrated science learning in schools and the integration of learning materials in integrated science books were still low. The solution to the problem was to use integrated science learning material of the excretory and respiratory system with a CTL strategy known as relating, experiencing, applying, cooperating, transferring or REACT. The purpose of this research was to determine the effect of using science learning material on the theme of the integrated excretory and respiratory system with REACT strategy to develop the academic performance of grade VIII students. The design of this research was a non-equivalent control group design with only posttest. The subject in this research was grade VIII students of SMPN 8 Padang. The instrument for collecting data consists of three parts, namely a multiple-choice written test to measure knowledge, an observation sheet to measure attitudes, and a performance assessment sheet to measure discovery skills.Research data for aspects of knowledge, attitudes, and discovery skills have a normal distribution and homogeneous variance. For this reason, a two-mean comparison test for two independent sample groups was used to determine differences in academic performance for these three aspects.The important result of this research is that the use of integrated science learning material with REACT strategy of the excretory and respiratory system theme has a significant effect on the academic performance of students in terms of knowledge, attitudes, and discovery skills